Fiscal Deficits, Public Debt, and Sovereign Bond Yields - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 2010)
The recent sharp increase in fiscal deficits and government debt in many countries raises questions regarding their impact on long-term sovereign bond yields. While economic theory suggests that this impact is likely to be adverse, empirical results have been less clear cut, have generally ignored nonlinear effects of deficits and debt through some other key determinants of yields, and have been mostly confined to advanced economies. This paper reexamines the impact of fiscal deficits and public debt on long-term interest rates during 1980 - 2008, taking into account a wide range of country-specific factors, for a panel of 31 advanced and emerging market economies. It finds that higher deficits and public debt lead to a significant increase in long-term interest rates, with the precise magnitude dependent on initial fiscal, institutional and other structural conditions, as well as spillovers from global financial markets. Taking into account these factors suggests that large fiscal deficits and public debts are likely to put substantial upward pressures on sovereign bond yields in many advanced economies over the medium term.